Potret Pandangan Warga Pesantren Terhadap Pro-Kontra Pelaksanaan Shalat Jum’at di Tengah Pandemi - Umi Mahmudah; Abdul Hamid; Awaludin Baharshah; Umum Budi Karyanto; Muhandis Az-Zuhri; Mohamad Dhoifan Fa’az (LPPM IAINU Kebumen, 2021)
The spread of the Corona virus outbreak has caused a lot of polemic in various elements of life, both social, cultural, economic, political and religious. In the religious field, a problem that has arisen and is widely discussed is the prohibition or suspension of Friday prayers. This policy cannot be separated from the pros and cons of the Indonesian people in particular. The purpose of this research is to find out the responses and views of Islamic boarding school residents towards government policies in general and the prohibition of Friday prayers in particular. The research uses a qualitative approach to provide a complete and comprehensive description. Data collection techniques were carried out by interviews/interviews and direct observation. Then, the data that has been obtained is analyzed descriptively. The results of the analysis indicate that most pesantren residents regret government policies because they are considered not optimal. Regarding the suspension of Friday prayers, they are of the view that Friday prayers will still be carried out even with a health protocol, they agree if the ban is applied to areas where it is